Effectiveness of obstacle-based and non-obstacle shooting training in petanque athletes - Fajri Hary Kurniawan; Rivan Saghita Pratama (Sriwijaya Journal of Sport, 2026)
Research Problems: Shooting accuracy is a fundamental skill in petanque that determines an athlete’s success in removing the opponent’s ball from the playing area. Therefore, an effective training model is required to improve this ability, one of which is through barrier and non-barrier shooting training methods. Research Objectives: This study aimed to analyze and compare the effectiveness of barrier and non-barrier training models on improving ball-to-ball shooting accuracy at a distance of 8 meters in petanque athletes. Methods: This study employed an experimental method with a two-group pretest-posttest design. The sample consisted of 10 petanque athletes from Salatiga City, selected using a total sampling technique, and was divided into two treatment groups. The first group received non-barrier shooting training, while the second group received barrier-based shooting training at an 8-meter distance for four weeks. Data were collected through a ball-to-ball shooting accuracy test before and after the treatment and analyzed using a normality test, paired sample t-test, and independent sample t-test at a significance level of 0.05. Results: The results showed that the barrier training group improved from a mean score of 3.00 to 9.60 with a significance value of 0.001 (p < 0.05), while the non-barrier group improved from 2.00 to 6.00 with a significance value of 0.014 (p < 0.05). However, the independent sample t-test indicated no significant difference between the two groups (p = 0.058 > 0.05), although descriptively the barrier group showed higher performance. Conclusion: The barrier training model is more effective in improving ball-to-ball shooting accuracy at an 8-meter distance compared to the non-barrier training model. Therefore, barrier-based training is recommended to be implemented in training programs to enhance throwing accuracy and directional control in petanque athletes.